2017
DOI: 10.5530/pj.2017.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on Angiotensin Converting Enzyme Inhibition, Antioxidant Activity, Total Phenolic Compound and Total Flavonoid of Peperomia pellucida Herbs Extract

Abstract: Introduction: Peperomia pellucida L. Kunth has been reported to have some biological activities such as antihypertensive and antioxidants. Herbal materials susceptible to contamination during processing and storage which can shortens their shelf life. Gamma-irradiation has been used as a method for preservation. Methods:This research aimed to analyze the effect of gamma-irradiation on inhibition activity of angiotensin converting enzyme (ACE), antioxidant activity, total phenol content, total flavonoid, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Based on the results of docking analysis, compound 5 has the most similar interaction with the captopril ligand where the compound binds to the active side of ACE as can be seen in Table 2, and these prediction results are in accordance with the molecular docking results of polyphenol compounds from Phyllanthus niruri herbs (Ahmad et al, 2018). In addition, some study has reported that extracts and fractions (with rich in polyphenol content) of this herbs have activity as an ACE inhibitor using in vitro assay method (Adhitia et al, 2017;Rinayanti et al, 2013;Saputri et al, 2015). Meanwhile, according to the previous study, Kurniawan et al (2016) have done the assay of ACE inhibitory activity of Compound 9 (quercetin) with IC 50 of 16.21 nM which has excellent correlation with the obtained docking result.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of docking analysis, compound 5 has the most similar interaction with the captopril ligand where the compound binds to the active side of ACE as can be seen in Table 2, and these prediction results are in accordance with the molecular docking results of polyphenol compounds from Phyllanthus niruri herbs (Ahmad et al, 2018). In addition, some study has reported that extracts and fractions (with rich in polyphenol content) of this herbs have activity as an ACE inhibitor using in vitro assay method (Adhitia et al, 2017;Rinayanti et al, 2013;Saputri et al, 2015). Meanwhile, according to the previous study, Kurniawan et al (2016) have done the assay of ACE inhibitory activity of Compound 9 (quercetin) with IC 50 of 16.21 nM which has excellent correlation with the obtained docking result.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that P. pellucida extract had total polyphenol and flavonoid content of 359.91±0.77 mg GAE/g extract and 200.28±1.23 mg QE/g extract, respectively. In the studies of Adhitia et al (2017), Ahmad et al (2018), andNg et al (2021), polyphenols and flavonoids were determined to be present in the plant. Therefore, it can be seen that P. pellucida is capable of synthesizing high content of total polyphenols and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…It is used ethnobotanically for treating cough, sores, boil, fracture, conjunctivitis, asthma, hypertension, urinary infection, gastro-intestinal disorder, kidney disease. Also, its pharmacological potential has been reported as anticancer, antibacterial, anti-inflammatory, analgesic, hypotensive, antidiabetic, fibrinolytic, antisickling and antidiarrhea (Adhitia et al, 2017). Phytochemical screening revealed that Peperomia pellucida contains glycosides, F I G U R E 1 Structures of some drugs used for managing hypertension anthraquinones, terpenoids and tannins (Saputri et al, 2015).…”
Section: Peperomia Pellucidamentioning
confidence: 99%
“…Their investigation revealed that the inhibitory effect of Peperomia pellucida was more potent than captopril (the reference drug used as positive control). Adhitia et al (2017) reported the ability of ethanol extract of Peperomia pellucida to inhibit ACE, an enzyme which activity is linked to hypertension. Their investigation revealed that subjecting the extract to about 10 kGy cobalt-60 radiation did not significantly affect its ability to inhibit ACE.…”
Section: Peperomia Pellucidamentioning
confidence: 99%